2019
DOI: 10.1111/joss.12531
|View full text |Cite
|
Sign up to set email alerts
|

Temporal profiling of simplified lemonade using temporal dominance of sensations and temporal check‐all‐that‐apply

Abstract: Given that little is known about how sensory interactions during lemonade consumption unfold over time, we studied the impact of citric acid level and type of sweetener on dynamic perception of simplified lemonade using temporal dominance of sensations (TDS) and temporal check‐all‐that‐apply (TCATA). We found that citric acid level did not impact perception of lemon flavor. Instead, the sweetener type had an impact on the rate and duration with which lemon flavor was perceived as dominant in TDS, but not its o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…Although the obtained results were generally similar for both methods, TDS highlighted a greater number of differences in sensory taste attribute perception between the two evaluation conditions. This observation has already been carried out in studies on liquid products [ 28 ]. The two methods therefore gave similar and complementary results, the weaknesses of TCATA being corrected by TDS, and conversely.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Although the obtained results were generally similar for both methods, TDS highlighted a greater number of differences in sensory taste attribute perception between the two evaluation conditions. This observation has already been carried out in studies on liquid products [ 28 ]. The two methods therefore gave similar and complementary results, the weaknesses of TCATA being corrected by TDS, and conversely.…”
Section: Discussionmentioning
confidence: 63%
“…The TDS and TCATA methods were used to study the dynamic sensory perception of liquid, semi-solid, or solid products [ 17 , 18 , 19 , 20 , 21 , 27 , 28 ]. However, these two methods have never been used to characterize the sensory properties of ODTs, for which the formulation leads to particular combinations and intensities of sensations not otherwise encountered in foods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the degree of pleasantness of the product initially increased and obtained a maximum ideal point of approximately 8–10% sucrose, after which the degree of pleasantness decreased. Other studies have also suggested that the relative optimal sweetness is the important driver of liking in sweetened sour beverages [ 18 , 19 , 20 ]. Additionally, Leksrisompong et al predicted that for both sweetness and mouth coating, the absences of bitter and metallic tastes function as consumer drivers of liking for lemon-lime carbonated beverage products [ 18 ].…”
Section: Resultsmentioning
confidence: 99%